2016
DOI: 10.1007/s40145-016-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of perovskite La0.8Sr0.2Ga0.83Mg0.17O2.815 electrolyte using a poly(vinyl alcohol) polymeric method

Abstract: Abstract:The perovskite La 0.8 Sr 0.2 Ga 0.83 Mg 0.17 O 2.815 (LSGM) fuel cell electrolyte was prepared by a polymeric method using poly(vinyl alcohol) (PVA). The LSGM precursor powder was examined by thermogravimetric and differential thermal analysis (TG/DTA) and Fourier transform infrared (FTIR) spectroscopy. It was found that thermal decomposition of the LSGM precursor powder occurs in a number of different stages, and complete decomposition of the precursor is obtained at 1000 ℃. X-ray diffraction (XRD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Consequently, the materials LaSrGa3O7, La4Ga2O9, and LaSrGaO4 have rather low ionic conductivity; their presence in the composition should negatively affect the ion transport of lanthanum gallate. This conclusion is supported by the results of Li et al [33], who found that the presence of LaSrGa3O7 (2.3 %) and LaSrGaO4 (2.3 %) phases in La0.8Sr0.2Ga0.83Mg0.17O3−δ ceramics leads to a decrease in conductivity at 800 °C from 8.24 • 10 −2 S/cm for the pure material to 1.28 • 10 −3 S/cm with impurities. Zhang et al [34] demonstrate a twofold decrease in the conductivity of ceramics from 3.95 • 10 −2 to 1.43 • 10 −2 S/cm in the presence of about 8 % of LaSrGaO4 and LaSrGa3O7 impurity phases.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Consequently, the materials LaSrGa3O7, La4Ga2O9, and LaSrGaO4 have rather low ionic conductivity; their presence in the composition should negatively affect the ion transport of lanthanum gallate. This conclusion is supported by the results of Li et al [33], who found that the presence of LaSrGa3O7 (2.3 %) and LaSrGaO4 (2.3 %) phases in La0.8Sr0.2Ga0.83Mg0.17O3−δ ceramics leads to a decrease in conductivity at 800 °C from 8.24 • 10 −2 S/cm for the pure material to 1.28 • 10 −3 S/cm with impurities. Zhang et al [34] demonstrate a twofold decrease in the conductivity of ceramics from 3.95 • 10 −2 to 1.43 • 10 −2 S/cm in the presence of about 8 % of LaSrGaO4 and LaSrGa3O7 impurity phases.…”
Section: Introductionsupporting
confidence: 76%
“…Hydrolysis of urea (NH2CONH2) produces NH4OH, which acts as a precipitator of La 3+ , Sr 2+ , Ga 3+ , and Mg 2+ ions to form the corresponding oxides and/or hydroxides. One of the most common methods for the synthesis of ceramic materials is the sol-gel method, which has various modifications depending on the type of complexing agent and initial reagents [33,[42][43][44]53].…”
Section: Strategies For the Reduction Of The Sintering Temperaturementioning
confidence: 99%
“…In this paper, TiO 2 powders were synthesized using the Pechini method, also known as the polymer precursor method, which is based on the formation of a polymer in which metal ions are incorporated. This method was used because it presents advantages such as high purity, good chemical homogeneity, low implantation cost, synthesis at low temperatures, and the possibility of obtaining powders with lower grain size [19,20]. The reagents used to obtain the powders are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%